Diversity, host association, and cocoon variability of reared Indian Microgastrinae (Hymenoptera: Braconidae) - Gupta, Ankita; Fernández-Triana, José L. (Zootaxa, 2014)
Nearly 3,500 specimens of microgastrine wasps (Hymenoptera: Braconidae) were reared during caterpillar surveys undertaken in 2010-2013 across India, covering 16 States and one Union Territory (Andaman & Nicobar islands), and deposited in the National Bureau of Agriculturally Important Insects, Bangalore, India. The caterpillar inventory recovered over two hundred morpho-species within 22 families of Lepidoptera and yielded 90+ morpho-species of microgastrine wasps distributed among 13 genera: Apanteles Förster, Buluka de Saeger, Cotesia Cameron, Diolcogaster Ashmead, Distatrix Mason, Dolichogenidea Viereck, Fornicia Brulle, Glyptapanteles Ashmead, Microgaster Latreille, Microplitis Förster, Neoclarkinella Rema & Narendran, Parapanteles Ashmead, and Protapanteles Ashmead. Records of hyperparasitoids are also included: Mokrzeckia menzeli Subba Rao (Pteromalidae), Pachyneuron groenlandicum (Holmgren) (Pteromalidae), Pediobius foveolatus (Crawford) (Eulophidae), Trichomalopsis thekkadiensis Sureshan & Narendran (Pteromalidae), Eurytoma sp., and Pediobius sp. (Eurytomidae). The present study adds eight new host records and provides illustrations of 40 species of wasps (including types). A comprehensive list of microgastrine genera, host caterpillar species, host plants, cocoon colour, structure and spinning pattern, and hyperparasitoids is provided. Numerous photographs of parasitized caterpillars, cocoons (number/arrangement), associated host plants, and adult wasps are also provided. The Indian species Deuterixys ruidus (Wilkinson, 1928) is transferred to the genus Cotesia based on the shape and sculpture of the first and second mediotergites: Cotesia ruidus (Wilkinson) comb. nov. Microgaster carinicollis Cameron is transferred to Microplitis, based on examination of first and second mediotergites, length of metatibia spurs, and size of metaxocoxa: Microplitis carinicollis (Cameron) stat. rev.